Four new species of Drymonia (Gesneriaceae) from South America: Tributes to inspirational leaders - John L. Clark (PhytoKeys)
Exploratory field expeditions and herbarium research have led to the discovery of four new species of Drymonia (Gesneriaceae), distinguished by laterally compressed corollas, elongate inflorescence axes, and a nomadic climbing habit. These species, found in Andean forests of Colombia, Ecuador, and Peru, are unique within the Gesneriaceae for bearing inflorescences on a leafless portion of the stem near the ground, while their foliage is restricted to the subcanopy. Named in honor of visionary and inspirational leaders dedicated to advancing conservation, science, and education, the new species are Drymonia clavijoiae J.L.Clark, sp. nov., D. katzensteiniae J.L.Clark, sp. nov., D. rominieckiae J.L.Clark, sp. nov., and D. silvaniae J.L.Clark, sp. nov.